Analisis Pengaruh Tingkat Pemahaman Manajemen Syariah Terhadap Efektivitas Organisasi Nonprofit - arief, muhammad fauzy (Jurnal Bisnis Digital, 2025)
This study aims to analyze the influence of the level of understanding of sharia management on the effectiveness of non-profit organizations. Non-profit organizations, especially those based on religion or social, are increasingly required to manage their activities professionally but still based on Islamic ethical and spiritual values. Sharia management, with principles such as amanah, justice, deliberation, and ihsan, is believed to be a framework that supports the achievement of overall organizational effectiveness. This study uses a quantitative approach with a survey method of 20 respondents who are managers and staff of non-profit organizations in several major cities in Indonesia. Data were collected through questionnaires that have been tested for validity and reliability.Data analysis was carried out using simple linear regression to test the effect of the independent variable (level of understanding of sharia management) on the dependent variable (organizational effectiveness). The results of the study indicate that there is a positive and significant influence between the level of understanding of sharia management on the effectiveness of non-profit organizations. Respondents with a higher understanding of sharia principles tend to show better organizational performance, in terms of work efficiency, goal achievement, and stakeholder satisfaction. This finding reinforces the importance of internalizing sharia values in organizational management, not only as a symbol of morality, but also as a strategic foundation in building a competitive and sustainable organization. This study provides implications for leaders of nonprofit organizations to pay more attention to training and strengthening sharia values in their internal management systems.